Low Mismatch Key Agreement Based on Wavelet-Transform Trend and Fuzzy Vault in Body Area Network - Yang Wu; Yongmei Sun; Lei Zhan; Yuefeng Ji (International Journal of Distributed Sensor Networks)
Body area network (BAN) is an emerging branch of wireless sensor networks for personalized applications in many fields, such as health monitoring. The services in BAN usually have a high requirement on security, especially for the medical diagnosis, which involves private information. With limitations of power and computation capabilities, one of the main challenges to ensure security in BAN is how to generate or distribute a shared key between nodes for lightweight symmetric cryptography. The current research almost exploits the randomness and distinctiveness (characteristics) of physiological signals to solve the key generation problem. However, it needs the help of additional hardware support and has the constraint on positions deployment, to acquire vital signals, which will bring the high cost and hardness to implementation of real system. To avoid the above problems, this paper presents a novel key generation scheme and a key distribution protocol, both of which are only based on wireless modules equipped on sensors. By exploiting the high correlation of received signal strength index (RSSI) between peer-to-peer communications, our scheme can provide a shared symmetric cryptographic key under the presence of an eavesdropper. We conduct experiments on the real Telosb nodes, and the results demonstrate that our proposed methods have a good performance on security.